Activation of FcRn Mediates a Primary Resistance Response to Sorafenib in Hepatocellular Carcinoma by Single-Cell RNA Sequencing - Xin Guan; Yi Wu; Shuqin Zhang; Zhiyi Liu; Qingjie Fan; Shuai Fang; Sennan Qiao; Fei Sun; Chongyang Liang (Frontiers Media S.A., 2021)
Sorafenib is the first-line therapeutic option for advanced hepatocellular carcinoma (HCC). Many patients exhibit a primary resistance (PR) response after initial treatment. In previous studies, compared to acquired resistance, the mechanism of PR is unclear. The present study aimed to evaluate the response of patient samples to sorafenib by patient-derived xenograft (PDX) models, and the differences at the transcriptome level between the sorafenib PR group and the sorafenib sensitive group were analyzed by single-cell sequencing technology. A specific cell cluster may be differentiated by the liver bud hepatic cells, and the JUN transcription factors in this cell cluster were highly activated. The albumin is secreted by other cell clusters, and the cluster stimulates the FcRn complex receptor to activate the HIF pathway and cell proliferation, resulting in a poor response to sorafenib. These findings are validated by both cell communication analysis and experiments. Thus, the current studies provided a novel approach for the treatment of sorafenib-resistant HCC.